INFLUENCE OF E-BEAM POSTHARVEST IRRADIATION IN THE COLOUR OF FOUR EUROPEAN CHESTNUT FRUIT VARIETIES OF CASTANEA SATIVA MILL - Amilcar L. Antonio; Marcio Carocho; Albino Bento; Andrezej Rafalski; Begona Quintana (European Scientific Journal, ESJ, 2013)
In this study we characterized the physical dimensions of four European chestnut varieties of Castanea sativa, 3 from Portugal (Cota, Longal and Judia) and 1 from Italy (Palummina). The typical physical dimensions of the different chestnut fruit varieties could be used to optimize the process in an irradiation preservation treatment. The chestnut fruits were submitted to an irradiation preservation treatmen with electron beam, at 1 kGy, and the colour parameters (CIE L*, a*, b*) of the skins, fruit and interior (half-cutted), were monitored after irradiation treatment and along 2 months of storage. We could conclude that e-beam irradiation, for the dose of 1 kilogray, did not induce any significant change in the skin, fruit and interior’s colour parameters.